Education in Law - Benavides Ganoza, Alberto (1978)
The aim of this paper is to analyze in a philosophical way education and its connection with law. In this sense, the etymology of philosophy and education are studied as points of reference, in order to highlight their importance and how their interrelation could influence the level of education in the legal field. In this way, it is concluded that an education in law should include philosophy as an attempt to form agents who are able to reflect and constantly seek creation and learning.